Why Did the Cod Wars Occur and Why Did Iceland Win Them? A Test of Four Theories - Sverrir Steinsson 1990- (2015)
Few attempts have been made to provide theoretical explanations for the occurrence and outcomes of the Cod Wars. In this thesis, I test hypotheses derived from four IR theories and perspectives on the Cod Wars: the Rationalist Explanations for War perspective, which sees information problems, commitment problems and issue indivisibility as drivers of conflict; Liberal IR theory, which expects democracy, commercial ties, and institutions as pacifying influences; Structural Realism, which expects states to pursue their security interests; and Neoclassical Realism, which expects statesmen’s pursuit of security interests to be distorted by domestic pressures. I find that Liberal and Structuralist Realist expectations were not met, that rational miscalculation and misinformation contributed to the occurrence of the disputes, and Neoclassical Realist expectations were fully met in all of the disputes. Following these tests, I provide a new, structurally informed explanation of the Cod Wars. The disputes occurred due to powerful domestic pressures on statesmen to escalate. As the disputes escalated and security interests were put at greater risk, British statesmen were able to make greater concessions due to weaker domestic constraints than those faced by Icelandic leaders. Iceland therefore reached a highly favorable agreement in all Cod Wars.